Penggunaan Metode Ganjaran dalam Meningkatkan Motivasi Belajar Bahasa Arab Siswa di MAS Bahrul Hikmah Konawe Utara Sultra - Gani, Yusnindar Abd; Wahidah, Yeni Lailatul (Journal of Islamic Education, 2021)
This study aims to reveal descriptively about the use of learning methods in improving students' learning motivation in Mas Bahrul Hikmah Konawe North Sultra to find out what methods are applied during the learning process at Mas Bahrul Hikmah Konawe Utara and to find out how the motivation of student learning Mas Bahrul Hikmah Konawe North.The method used in this research is descriptive qualitative method in order to give explanation about the use of learning method in improving students' learning motivation Arabic in Mas Bahrul Hikmah Konawe Utara Sultra. The data obtained through interviews with informants research related to the achievement of the purposes of research. Subjects in this study were teachers and students at Mas Bahrul Hikmah Konawe Utara Sultra.The result of the research are: 1) The method applied when the learning process of Arabic language in Mas Bahrul Hikmah is, conversation method or muhadatsah, the method of reading that is qira'ah (muthala'ah), grammatical method or qowa'id (al-kitabah) and Listening method (al-istima'i) this method is commonly used when imla learning process, besides using special method of learning Arabic language also using general methods, such as lecture method, discussion method, group work method, question and answer method and method Assignment. There is also a new method addition, reward method. The reward method applied is the method of punishment and reward method. 2) The use of reward method in Mas Bahrul Hikmah is very effective besides can grow student's motivation in learning also help student get high test value, because after use method of reward value of student exam much increase